HOMESTAY DI NAGARI TUO PARIANGAN: SEJARAH DAN PERKEMBANGANNYA 2015-2024 - Fatwa, Sakinah Putri; Fatimah, Siti (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
Nagari Tuo Pariangan is the oldest village in Minangkabau, located in Tanah Datar Regency, West Sumatra. This village is rich in natural resources, culture, and history. In 2012, this village was recognized as one of the most beautiful villages in the world by a budget travel magazine. This recognition has had a positive impact on tourism in this village, with an increase in the number of tourists visiting Nagari Tuo Pariangan. The increase in tourism activity in Nagari Tuo Pariangan has encouraged the conversion of traditional houses into homestays as a form of community adaptation to the economic potential of tourism. This study aims to examine the early history of the emergence of homestays in Nagari Tuo Pariangan and analyze their development until 2024. This study uses a historical research method consisting of four stages: heuristics, source criticism, interpretation, and historiography. The results of this study indicate that homestays began to develop since 2015 in response to the increase in tourists. This development is marked by an increase in the number of homestays, community involvement, and a stronger cultural element in guest services. Homestays in Nagari Tuo Pariangan are not only a place to stay, but also help preserve culture and improve community welfare through tourism.